2019
DOI: 10.1080/1478422x.2019.1600836
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between microstructure and corrosion behaviour of Bi-Zn solder alloys

Abstract: Bi-Zn solder alloys with different Zn contents (1.5, 2.7 and 5wt-%) were prepared by casting and the correlation between the microstructure and corrosion behaviour by mean of direct current electrochemical tests was studied. The surface analysis of the hypoeutectic Bi-Zn alloy samples revealed the presence of needle-like ZnO and very small agglomerated spherical particles. By contrast, eutectic alloy presented the formation of a uniform and compact film of ZnO, which is related to the better distribution of Zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…[53][54][55][56][57][58] Despite many studies having found equations given by λ 2 ¼ constant (V ) À2/3 for different alloy systems, [59][60][61][62] the effects of lateral solute segregation on the wavelengths of instabilities along the sides of primary dendritic stems for Bi-based alloys are still not well understood. Herein, a single power law in which the exponent À1.1 characterizes the experimental evolution of λ 2 as a function of V L for all Bi- (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) wt% Sb alloys is proposed. Figure 10 shows Vickers microhardness (HV) for the analyzed Bi-Sb alloys as a function of Sb concentration along the length of DS castings, highlighting the solidification microstructure morphologies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[53][54][55][56][57][58] Despite many studies having found equations given by λ 2 ¼ constant (V ) À2/3 for different alloy systems, [59][60][61][62] the effects of lateral solute segregation on the wavelengths of instabilities along the sides of primary dendritic stems for Bi-based alloys are still not well understood. Herein, a single power law in which the exponent À1.1 characterizes the experimental evolution of λ 2 as a function of V L for all Bi- (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) wt% Sb alloys is proposed. Figure 10 shows Vickers microhardness (HV) for the analyzed Bi-Sb alloys as a function of Sb concentration along the length of DS castings, highlighting the solidification microstructure morphologies.…”
Section: Resultsmentioning
confidence: 99%
“…irregular shape ! trigonal pattern) to be identified in Bi- (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) wt% Sb alloys as the solute content increases. 2) Although a general power-type experimental law given by λ 1 ¼ constant (Ṫ) À0.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In HCl solution, the corrosion rate of WM is the highest because of the largest grain size and the lowest hardness. Low hardness metals are known to have low corrosion resistance [29][30][31]. In addition, the formed precipitates during the welding process contribute to the highest corrosion rate in the WM zone [32].…”
Section: Discussionmentioning
confidence: 99%